Pengaruh Pembelajaran Kooperatif Tipe Numbered Head Together dan Make A Match Terhadap Prestasi Belajar Sistem Komputer Ditinjau dari Kecerdasan Emosional - Imam Afandi; Budiyono Budiyono; Sunardi Sunardi (Universitas Sebelas Maret, 2017)
The teacher's role is only as a facilitator, mediator and guide. Because the approach used is student-centered, the teacher only assists the change process with scaffolding and guiding so students can achieve a more perfect understanding than previous understanding. The Cooperative Learning model is one of the learning models that emphasizes the active role of students in learning. Among the cooperative learning models are the type of NHT and Make A Match. This research is an experimental research, 2x3 factorial design. The Population of this research is all of vocational school students in Sub Rayon 1 of Ngawi Regency in Odd Semesterof Academic Year 2013/2014. Research is done by providing the same learning materials for experimentation and control classes. Experimental Classes with the NHT Cooperative Model Approach while the control classes used the Make A Match Cooperative Model Approach. The results are (1) there is a difference in effect between the use of the NHT (Numbered Head Together) type of cooperative learning model and Make a Match on student achievement. (2). There are differences in the learning achievements of students who have high, moderate and low emotional intelligence on computer system subjects. (3). There is an interaction of influencebetween the use of NHT cooperative learning models and Make a Match with the level of emotional intelligence of students on student achievement in Computer System subjects in terms of students' emotional intelligence.